Legal Protection of Investors from the Corporate Malfeasance of Insider Dealings: A South African-Canadian Comparative Review - M. Oluyeju; O. Oluyeju (BRICS Law Journal, 2022)
Ensuring market discipline, integrity, and transparency with the overall aim of protecting the investing public is critical to the wellness of a capital market and a financial system. However, one corporate ill besetting the securities markets in all jurisdictions is insider trading. Apart from being unethical, insider trading disrupts market dynamics. In South Africa, over the years, successive Acts have been enacted, amended, and repealed to ensure discipline and protect the integrity of the nation’s securities market. In 2012, the Financial Markets Act of 2012 (FMA) was enacted to improve, among others, the enforcement of insider trading regulation in South Africa. However, the regulation of insider trading and its enforcement in terms of the FMA have been insufficient. This article therefore seeks to benchmark the South African position against Canadian model with the objective of drawing lessons for South Africa. The choice of Canada was informed by the fact that Canada has a well-developed anti-insider trading regulatory framework and presents a case study of international best practices in the regulation of insider trading. Therefore, the conclusion in this article is that with creative and appropriate reforms of the FMA, using the Canadian model, the investing public will be adequately protected against insider trading, and investors’ confidence and the financial markets’ integrity and efficiency will be better enhanced.